Cell proliferation and neurogenesis in the adult telencephalon of the newt Cynops pyrrhogaster. (30th November 2022) - Iwasa, Ami; Hanaoka, Naoki; Ohwada, Kosuke; Iwamuro, Shawichi; Toyoda, Fumiyo; Kikuyama, Sakae; Hasunuma, Itaru
Abstract: Urodele amphibians have the ability to regenerate several organs, including the brain. For this reason, the research on neurogenesis in these species after ablation of some parts of the brain has markedly progressed. However, detailed information on the characteristics and fate of proliferated cells as well as the function of newly generated neurons under normal conditions is still limited. In this study, we focused on investigating the proliferative and neurogenic zones as well as the fate of proliferated cells in the adult brain of the Japanese red‐bellied newt to clarify the significance of neurogenesis in adulthood. We found that the proximal region of the lateral ventricles in the telencephalon and the preoptic area in the diencephalon were the main sites for continuous cell proliferation in the adult brain. Furthermore, we characterized proliferative cells and analyzed neurogenesis through a combination of 5‐ethynyl‐2′‐deoxyuridine (EdU) labeling and immunohistochemistry using antibodies against the stem cell marker Sox2 and neuronal marker NeuN. Twenty‐four hours after EdU injection, most of the EdU‐positive cells were Sox2‐immunopositive, whereas, EdU‐positive signals and NeuN‐immunoreactivities were not colocalized. Two months after EdU injection, the colocalization ratio of EdU‐positive signals with Sox2‐immunoreactivities decreased to approximately 10%, whereas the ratio of colocalization of EdU‐positive signals with NeuN‐immunoreactivities increased to approximately 60%. Furthermore, a portion of the EdU‐incorporated cells developed into γ‐aminobutyric acid‐producing cells, which are assumed to function as interneurons. On the basis of these results, the significance of newly generated neurons was discussed with special reference to their reproductive behavior. Abstract : We investigated cell proliferation sites in the adult brain of the Japanese red‐bellied newt ( Cynops pyrrhogaster ). Furthermore, we quantitatively analyzed the neurogenesis in the telencephalon and demonstrated that a number of newly generated neurons are assumed to be GABA‐producing interneurons. On the basis of the results, we discussed relationship between the neurogenesis and reproduction in the newt.